Análisis y control del cumplimiento tributarío en el ejercicio fiscal 2008 de una empresa localizada en la ciudad de Guayaquil que se dedica a la elaboración, producción y exportación de aceite de pescado - Tigrero C., Pedro (2009)
Taxes (Tributes) are the social benefits that the State or an authorized public entity for the purpose by that one, demand of cost-reducing submitted subjects at the same. In this work will show the description of the company, his processes, likewise as the analysis of the countable situation. The main purpose is to verify if such countable procedures fulfill with the tributaries, with his tributaries obligations in the fiscal period 2008, through the analysis of the accounts and the conciliations of the statements realized to the SRI and the countable registers. It will realize in compliance with Auditoria's standards Generally Accepted, the Principles of Accounting Generally Accepted, and the Tributaries Laws to be able to make a correct analysis of the tributary fulfillment corresponding to the fiscal year 2008, of a commercial company placed at Guayaquil's city, dedicated to the Elaboration, Production and Exportation of fish´s oil.